Growth Strategy untuk Meningkatkan Daya Saing Koperasi Peternakan Bandung Selatan (KPBS) Pangalengan - Wulan Sari Dewi; Salsabila Hafizhah; Vika Aprianti (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2023)
This study aims to provide business strategy proposals to increase competitiveness in the South Bandung Animal Husbandry Cooperative (Koperasi Peternakan Bandung Selatan/KPBS) Pangalengan, with a series of tools used to analyze the company's environment, strategy formulation, and selection of the best strategy. The research method uses a quantitative approach to analyze conditions, determine internal and external environmental phenomena, formulate alternative strategies using SWOT analysis with BCG Matrix (Modified), GE Matrix (Original) and TOWS matrix mapping. The results of the study revealed an IFAS score of 4.9 and an EFAS of 5.52 (both above 2.5 (midpoint)). This states PT. KPBS Pangalengan is able to overcome strengths, weaknesses, opportunities and threats. Furthermore, the Alternative Strategy obtained that the priority strategy proposed for PT. Susu KPBS Pangalengan namely Growth Strategy, a strategy that focuses on fast growth, the company can strengthen its position in the market and increase market share by expanding geographical area or adding product lines.